Mapping waiata koroua (traditional prose) of the Tarawera Eruption, 1886; and its relevance to contemporary natural hazards preparedness and response : a thesis presented in fulfilment of the requirements for the degree of Masters of Emergency Management at Massey University, Wellington, New Zealand - Tapuke, Sylvia Hiriwa (Massey University, 2017)
This qualitative study maps two waiata koroua about the Tarawera Eruption, 1886, through the experience of Ngāti Haka-Patuheuheu, and directly affected tribes. This research includes a two-day wānanga (cultural learning programme), hui (traditional meeting), whakawhiti kōrero (informal discussions) and semi-structured interviews with Tūhoe, Ngāti Haka-Patuheuheu, and Te Arawa tribal members.
The thesis will be uploaded in due course.
Keywords: Emergency management; New Zealand; Tarawera, Mount (N.Z.); Eruption, 1886; Maori (New Zealand people); History; 19th century; Songs and music; Waiata koroua; Kōrero nehe; Aituā (Taiao); Māori Masters Thesis; 350703 Disaster and emergency management; 450706 Te hītori ahurea Māori (Māori cultural history)